The synthesis of zirconium oxide (ZrO2) nanoparticles (NPs) in 1-butyl-3-methylimidazolium trifluoroacetate (BMIMCF3COO) for an amperometry phenol biosensor - Tapak, Nurul Syafiqah; Nawawi, Mohd Azizi; Tan, Eddie Ti Tjih; Mohd, Yusairie; Ab Rashid, Ahmad Hazri; Abdullah, Jaafar; Yusof, Nor Azah; Ahmad, Nor Monica (Elsevier, 2022)
A novel zirconium oxide (ZrO2) nanoparticles (NPs) was synthesised utilising 1-butyl-3-methylimidazolium trifluoroacetate (BmimCF3COO) as an effective capping agent to reduce agglomeration and further improve the size of the developed NPs. The purity and properties of the ZrO2 NPs were assessed through characterisation with Fourier-transform infra-red, ultraviolet-visible, transmission electron microscopy, field emission scanning electron microscopy-energy dispersive X-ray (FESEM-EDX), and X-ray diffraction. Subsequently, the ZrO2 NPs was incorporated on the modified screen-printed carbon electrode (SPCE) via glutaraldehyde (GA) cross-linking before immobilisation of tyrosinase (Tyr). Cyclic voltammetry and FESEM-EDX were selected to investigate the electrochemical properties and surface morphology of modified carbon SPCE. The surface of a modified electrode demonstrated a larger coagulant with significant porosity due to the nano-sized of ZrO2. The electrocatalytic response of the resulting ZrO2 NPs/GA/Tyr to phenol was evaluated by employing the chronoamperometry method. The resultant current response was compared to the phenol concentration from the reduced quinone formation on the modified electrode surface. The developed biosensor exhibited excellent linearity for phenol within the 10 and 90 µM (R2 = 0.9907) range with sensitivity and limit of detection (LOD) of 10.522 µA/mM and 9.468 µM, respectively, under optimal conditions. The bioelectrode exhibits satisfactory percent recovery (75–125 %) using spiked water samples from rivers and industries. Moreover, the biosensor demonstrated reasonable repeatability, reproducibility, anti-interference properties, high sensitivity, and tremendous storage stability for at least 20 days. The accomplishment of the as-prepared phenol biosensor could pave the way for a portable diagnostics strategy for rapid detection of phenol in the water sample.